Unveiling the multifaceted roles of microRNAs in extracellular vesicles derived from mesenchymal stem cells: implications in tumor progression and therapeutic interventions - Hu, Sujia; Zhang, Chang; Ma, Qianhui; Li, Minghe; Yu, Xiao; Zhang, Haiying; Lv, Shuang; Shi, Yingai; He, Xu (Frontiers in Pharmacology, 2024)
Abstract: Mesenchymal stem/stromal cells (MSCs) have the capacity to migrate to tumor sites in vivo and transmit paracrine signals by secreting extracellular vesicles (EVs) to regulate tumor biological behaviors. MSC-derived EVs (MSC-EVs) have similar tumor tropism and pro- or anti-tumorigenesis as their parental cells and exhibit superior properties in drug delivery. MSC-EVs can transfer microRNAs (miRNAs) to tumor cells, thereby manipulating multiple key cancer-related pathways, and further playing a vital role in the tumor growth, metastasis, drug resistance and other aspects. In addition, tumor cells can also influence the behaviors of MSCs in the tumor microenvironment (TME), orchestrating this regulatory process via miRNAs in EVs (EV-miRNAs). Clarifying the specific mechanism by which MSC-derived EV-miRNAs regulate tumor progression, as well as investigating the roles of EV-miRNAs in the TME will contribute to their applications in tumor pharmacotherapy. This article mainly reviews the multifaceted roles and mechanism of miRNAs in MSC-EVs affecting tumor progression, the crosstalk between MSCs and tumor cells caused by EV-miRNAs in the TME. Eventually, the clinical applications of miRNAs in MSC-EVs in tumor therapeutics are illustrated.